Association between adherence to the Mediterranean diet and renal function biomarkers and cardiovascular risk factors among diabetic patients with nephropathy. (December 2020) - Moradi, Maedeh; Daneshzad, Elnaz; Najafabadi, Mozhgan Mortazavi; Bellissimo, Nick; Suitor, Katherine; Azadbakht, Leila
Summary: Background and aim: Although the relationship between a Mediterranean diet (Med diet) and cardiovascular disease (CVD) risk factors has been widely established, no reports exist regarding this association in patients with Diabetes Nephropathy (DN). The aim of this study was to determine the association between level of adherence to a Med diet and renal and CVD risk factors among patients with DN. Study design: A cross-sectional study. Methods: The current study was conducted in 270 patients with DN. A validated food frequency questionnaire was used to assess dietary intake. The Med diet score was determined based on the eight characteristics of a traditional Med diet. Anthropometrics, fasting blood glucose (FBS), total cholesterol (TC), low-density lipoproteins (LDL-c), triacylglycerol (TG), hemoglobin A1C (HbA1c), creatinine (Cr) and blood urea nitrogen (BUN) were detected using standard methods. Kidney function was estimated using the Modification of Diet in Renal Disease (MDRD) formula for estimated glomerular filtration rate (eGFR). Results: In fully-adjusted models, high serum TC and diastolic blood pressure (DBP) were reduced in participants that demonstrated a greater adherence to a Med diet, but did not reach statistical significance (OR: 0.20; 95% CI: 0.01, 5.52; P = 0.299; OR: 0.81; 95% CI: 0.28, 2.36; P = 0.667). Waist circumference (WC) was non-significantly lower in male participants (OR: 0.91; 95% CI: 0.27, 3.05; P = 0.889). Greater compliance with a Med diet showed a non-significant reduced risk for increased bodyweight (OR: 0.82; 95% CI: 0.23, 2.85; P = 0.730) and obesity (OR: 0.45; 95% CI: 0.03, 6.06; P = 0.493). Conclusion: Adherence to a Med diet was not significantly associated with cardiovascular risk factors and renal function among patients with Diabetes Nephropathy.